(NsOBRANIE SO^INENIJ W ^ETYREH TOMAH(B; s (NrASSKAZY(B. (No^ERKI(B. (NkORRESPONDENCII (B/ s (N~ASTX (B2s - (NsERAFIMOWI^(B, (NaLEKSANDRs ((NmOSKWA(B: s (NpRAWDA(B, s, 1987)
(NwO WTOROJ TOM WO[LI RASSKAZY(B, (NO^ERKI I KORRESPONDENCII(B.s
rus
Keywords: (NrASSKAZY(B, (NPOWESTIs; (No^ERKIs -- (NkORRESPONDENCIIs